Microbially driven microplastic degradation: From mining functional microbiota to enhancing remediation potential in diverse environments - Xin Hou; Ruijia Jing; Yunan Lin; Ziwei Chen; Changjun Li; Zhiyun Wang; Xianhua Liu (Journal of Hazardous Materials, 2026)

Post-cyclic undrained behaviour of marine soft clay under cyclic loading with variable confining pressure - Junhao Tong; Dongyang Yuan; Changjun Li; Haozheng Wang; Dingyu Ni; Ke Wu; Pixian Si; Qiang Wang; Lin Guo (Marine Georesources & Geotechnology, 2026)

Regulating organic loading to mitigate the impact of microplastics on nitrogen removal and microbial communities in SBR systems - Yi Yang; Lin Luo; Jian Zhu; Kai Deng; Changjun Li; Ying Zhang; Zhongxiang He; Pofei Wang; Hua Peng (Journal of Water Process Engineering, 2025)

One-step microwave method synthesis of N, S-codoped carbon with the frustrated Lewis pairs for Cr (VI) removal - Liwen Wang; Yixin Sha; Changjun Bi; Daoqing Lin; Yuxue Liu; Lichun Dai; Xiaozhi Wang; Hui Lin; Jawad Ahmad Jrar; Jianhua Hou (Journal of Water Process Engineering, 2025)

Baicalin attenuates acute skin damage induced by ultraviolet B via inhibiting pyroptosis - Zuohao Liu; Bingrong Dang; Zhen Li; Xingsheng Wang; Yuhan Liu; Fen Wu; Xinhui Cao; Chunming Wang; Changjun Lin (Journal of Photochemistry and Photobiology B: Biology, 2024)

Three thousand years of Hg pollution recorded in mangrove wetland sediments from South China - Minqi Chen; Bigyan Neupane; Xuan Zhan; Ting Liu; Zhanyi Lin; Changjun Gao; Claudio Zaccone; Kunshan Bao (Environmental Research, 2024)

A three-modal fluorescent sensor harnessing diverse luminescent mechanisms for the purpose of segmented Baijiu identification - Lin Chen; Zhenyu Mao; Yi Ma; Huibo Luo; Suyi Zhang; Danqun Huo; Changjun Hou (Food Chemistry, 2024)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

Mechanical properties and constitutive model of high-abundance methane hydrates containing clayey–silt sediments - Fan Yang; Changjun Li; Na Wei; Wenlong Jia; Jie He; Shuoshuo Song; Yuanrui Zhang; Youzhi Lin (Ocean Engineering, 2024)

Effects of poplar agroforestry systems on soil nutrient and enzyme activity in the coastal region of eastern China - Cheng Xu; Zhuangzhuang Qian; Bo Wang; Tao Yang; Zeyang Lin; Di Tian; Changjun Ding; Luozhong Tang (Journal of Soils and Sediments, 2023)

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

The bacterial RNA ligase RtcB accelerates the repair process of fragmented rRNA upon releasing the antibiotic stress - Muhammad Ramzan Manwar; Changjun Shao; Xing Shi; Jian Wang; Qiang Lin; Yigang Tong; Yu Kang; Jun Yu (Science China Life Sciences, 2020)

Proteomic Analysis of Vibrio parahaemolyticus Under Cold Stress - Jing Tang; Juntao Jia; Ying Chen; Xiaohua Huang; Xiaoliang Zhang; Liqing Zhao; Wei Hu; Changjun Wang; Chao Lin; Zhenxing Wu (Current Microbiology, 2018)

Baseline sensitivity and control efficacy of flutolanil in Rhizoctonia solani - Shandong Li; Yiping Hou; Di Peng; Lin Meng; Jianxin Wang; Mingguo Zhou; Changjun Chen (Australasian Plant Pathology, 2014)

The polymorphisms of IL-4, IL-4R and IL-13 genes and bladder cancer risk in a Chinese population: a case–control study - Haiyan Chu; Lan Ma; Meilin Wang; Danni Shi; Chao Qin; Lin Yuan; Changjun Yin; Zhengdong Zhang (Molecular Biology Reports, 2012)

Involvement of histone hypoacetylation in Ni2+-induced bcl-2 down-regulation and human hepatoma cell apoptosis - Jiuhong Kang; Dawei Zhang; Jie Chen; Changjun Lin; Qing Liu (JBIC Journal of Biological Inorganic Chemistry, 2004)